miR-483-3p, Mediated by KLF9, Functions as Tumor Suppressor in Testicular Seminoma via Targeting MMP9 - Zhang, Lei; Ruan, Yashi; Qin, Zhiqiang; Gao, Xian; Xu, Kai; Shi, Xiaokai; Gao, Shenglin; Liu, Shouyong; Zhu, Kai; Wang, Wei; Zuo, Li; Zhang, Lifeng; et al. (Frontiers in Oncology, 2021)
Seminoma (SEM) is the most frequent testicular germ cell tumor with a high incidence in young men. Besides, many miRNAs have been identified as important regulators and biomarkers of testicular SEM. Nevertheless, the functional contributions of miR-483-3p to SEM remain unclear. Thus, the present study aims to explore the function and regulatory mechanism of miR-483-3p in SEM. miR-483-3p was down‐regulated in SEM tissues versus paracancerous normal tissues. The expression level of miR-483-3p was significantly associated with tumor stage by RT-qPCR. Functionally, miR-483-3p over-expression suppressed cell growth, migration and invasion in SEM cell lines. Mechanically, miR-483-3p negatively regulated MMP9 by directly binding to its 3’-UTR. The over-expression of miR-483-3p could reverse the promoting role of MMP9 over-expression on the proliferation, migration and invasion of TCam-2 cells. Moreover, KLF9 was an upstream regulator of miR-483-3p. In general, our study suggested that miR-483-3p could inhibit the cell growth, migration and invasion of testicular SEM by targeting MMP9. Moreover, KLF9 is an upstream positive regulator of miR-483-3p and also functions as a tumor suppressor in SEM.